Role of Transcription Factors in Banana Fruit Ripening: A Systematic Literature Review - Ayuwaningsih, Melina Siska; Setiati, Ning; Anggraito, Yustinus Ulung (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The development of edible fruit quality is a vital process. Banana fruit ripening is a complex biochemical and physiological process that causes physical changes such as softening. Fruit aging and ripening are greatly influenced by transcriptional regulation. Transcription factors also play an essential role in regulating various biological processes. Therefore, this study aimed to explore information about the role of transcription factors in banana fruit ripening. Methods: A systematic review was conducted by searching the Scopus database indexed Q1-Q4 through the Watase UAKE application from 2018 to 2023 to find relevant studies on the role of transcription factors in banana fruit ripening. Results: From the search results, 157 articles were found, which were then narrowed down to 11 articles by considering the established inclusion criteria. This study identified 11 transcription factors that have the potential for fruit ripening. Conclusions: The findings of this article review indicate that there are transcription factors, namely MYB, MaWRKY49, MabHLH7, MaNAC42, MaMADS36, bZIP21, MaMYB3, MabHLH, MaERF012, NAC, and WRKY. The role of transcription factors can control fruit quality in agricultural commodities that play genetics in molecular biology. These findings indicate that knowledge of the role of transcription factors can provide insight into the development of innovations in agriculture in the future.